Accelerated growth of Kappaphycus alvarezii using Sargassum aquifolium extract and its anatomical characteristics (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Cokrowati N, Risjani Y, Firdaus M, Andayani S. 2021. Accelerated growth of Kappaphycus alvarezii using Sargassum aquifolium extract and its anatomical characteristics. Biodiversitas 22: 5195-5202. Cultivation of Kappaphycus alvarezii seaweed has been carried out in Ekas Bay of Jerowaru Sub-district, East Lombok, West Nusa Tenggara, Indonesia but its production has decreased in the last three years due to its slow growth. In 2014, seaweed production was 1,882,875.50 tons and in 2017 it was 1,037,000 tons. Efforts are needed to increase growth by providing growth triggers from marine natural ingredients, namely Sargassum aquifolium. These brown algae can be found in the waters of Ekas Bay, the numbers are abundant and untapped. The purpose of this study was to analyze the growth of K. alvarezii given S. aquifolium extract. This research was conducted in the waters of Ekas Bay. The method used is experimental. The experimental design used was a completely randomized design with different treatments of K. alvarezii soaking time using S. aquifolium extract. The results showed that the growth of K. alvarezii given S. aquifolium extract increased and was significantly different between treatments. The highest absolute weight was 479 g in treatment A (soaking for 2 hours) and the lowest absolute weight was 181.25 g in treatment K (control). The highest growth rate occurred on the 18th day, namely 9.24% and the lowest was in the K treatment (control) which was 1.3%.
Keywords: Macroalgae; Brown algae; Phytohormones; Extracts; Growth